2020
DOI: 10.1097/scs.0000000000006838
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes in the Treatment of Isolated Sagittal Synostosis: Cranial Vault Remodeling Versus Spring Mediated Cranioplasty

Abstract: Background: Patients undergoing cranial expansion including spring-mediated cranioplasty (SMC) and cranial vault remodeling (CVR) receive costly and high acuity post-operative intensive care (ICU) given concerns over neurologic and hemodynamic vulnerability. The authors analyzed perioperative and post-operative events for patients presenting with sagittal craniosynostosis (CS) undergoing SMC and CVR in order to compare complication profiles. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The reported rate of postoperative hematoma in the literature is between 1% and 2%. 56,57 This rate remains consistent with the overall rate (0.9%) of postoperative hematoma for the same surgeon when considering the current series of 45 patients and the one previously published in 2023. 37 Our study showed a significant difference regarding cost minimization in the ERAS group (18,936 CHF) compared to the pre-ERAS group (21,958 CHF) (p = 0.029).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reported rate of postoperative hematoma in the literature is between 1% and 2%. 56,57 This rate remains consistent with the overall rate (0.9%) of postoperative hematoma for the same surgeon when considering the current series of 45 patients and the one previously published in 2023. 37 Our study showed a significant difference regarding cost minimization in the ERAS group (18,936 CHF) compared to the pre-ERAS group (21,958 CHF) (p = 0.029).…”
Section: Discussionsupporting
confidence: 90%
“…The rate of complications in our series is in line with what is reported in the literature. 56,57 It is relevant to emphasize that we did not encounter any anemia in the ERAS group. The systematic administration of tranexamic acid was associated with a reduction in blood loss and transfusions in the literature, 58 and our adherence to the whole ERAS protocol helped in limiting the incidence of anemia in our group of patients.…”
Section: Discussionmentioning
confidence: 66%
“…Multiple factors must be considered when weighing early intervention with strip craniectomy and spring-mediated cranioplasty or molding orthosis versus whole-vault cranioplasty for children with sagittal craniosynostosis. 36–40 This study using OCT technology concluded that elevated ICP appears to be very uncommon when minimally invasive surgical correction is undertaken earlier than 6 months of age, whereas children older than 6 months have a significantly higher likelihood of elevated ICP. We believe that this adds to the potential advantages of earlier intervention in patients who present in the first 6 months of life, acknowledging the importance of further research to clarify the relationship between ICP and neurocognitive outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…One recent study of perioperative risks following SMC suggested that routine standard postoperative care in the ICU for SMC may be discontinued because of low complication rates. 30 While a clear relationship between age and intracranial pressure (ICP) has not yet been identified in patients with craniosynostosis, it has been reported that patients under 1 year of age are less likely to have elevated ICP. [31][32][33][34] Surgical correction of craniosynostosis at an early age offers the advantage of preventing an elevation in ICP and the neurological sequelae.…”
Section: Discussionmentioning
confidence: 99%